LEGITIMIZING POLITICAL REGIME „THIRD WAVE” DEMOCRATIZATION - Shapovalenko, M.V. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
Dramatic dispersion of regime outcomes after an initial transition to competitive regimes has occurred in many parts of the world in the third and fourth waves of democratization. Many transitions to competitive regimes failed, resulting in a burgeoning number of competitive authoritarian regimes that sponsor controlled elections. Some regimes have status hybrid regimes. Freedom House’s monitoring shows that Ukraine is hybrid regime. Political system of Ukraine is very instability and fragile under external factor. This article is devoted to analysis of some features of political institutions. Permanent political crisis during several years increases potential risks for Ukrainian independent and authoritarian tendencies.